AI Act as EU Legislator’s Response to Challenges of Artificial Intelligence Development - Monika Wyszomirska (Safety & Fire Technology, 2025)
Aim: The legal regulation of artificial intelligence (AI) is one of the most pressing challenges of modern legislation. In response, the European Union has developed the first comprehensive AI regulation, the AI Act, which is based on risk analysis. The author, while appreciating the completeness of the EU regulation’s approach, draws attention to its limitations, including the risk of over-regulation, definitional ambiguities, lack of liability provisions, as well as limited flexibility in relation to technological developments. In view of the above, she proposes flexible tools for regulating AI in the form of legislative sandboxes and soft law, which enable legislators to react more quickly to technological changes. Introduction: In the context of the rapid development of artificial intelligence (AI) and the associated risks, it is crucial to consider how AI systems are marketed and used. In this article, the author analyses the main challenges of AI regulation, highlighting the difficulties of defining AI, protecting human rights, ensuring algorithmic transparency, and balancing the innovation of this technology with human and environmental safety. This publication is a continuation of a series of articles on the challenges posed to national and EU legislators by the rapid development of new technologies. In the previous articles published in SFT, the author discussed the legal aspects related to the development and implementation of new technologies and answered the question of whether the current legislation combines the intentions of the lawmakers with social and economic needs. Methodology: The study employs theoretical research methods, including an analysis of national and EU legislation. These considerations are complemented by literature on the subject and the views of experts in the field. The publication also draws on the author’s own research findings. Conclusions: The article discusses the main concepts of the Artificial Intelligence Regulation with a focus on the classification of AI systems, the obligations imposed on their providers and the role of legislative sandboxes. It also points to unresolved issues of legal liability, technological control and enforcement internationally. The author emphasises the need for a hybrid approach to AI regulation, taking into account both legal and socio-ethical contexts. Keywords: artificial intelligence, new technology law, cyber security, legislative sandboxes, soft law, AI systems